Perceived Value Added Tax (VAT) Compliance in Nepal - Sha, Binod; Singh, Sanju Kumar (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
These research willpowers consider the perceived VAT compliance for VAT collection in Nepal. The specific objectives are: analysis of the perceived VAT compliance for collection and current status of VAT of Government of Nepal. The study follows descriptive and explanatory research designs to explore the VAT compliance and its problems, prospects, policies and the ability of the Government of Nepal to collect VAT. The current study has based on primary data to measure perceived VAT compliance for VAT collection and status of the VAT conducting field survey using pre-structured questionnaires. Altogether 400 respondents from the four categories are interviewed: 100 from VAT payers, 100 from VAT administration, 100 from VAT experts and 100 from business community all over the country, respondents were requested to indicate their degree of conformity with specified statements using 5-point scale. The regression results of perceived issues show that the sign of all the independent variables are as per priority and expectation. The computed F-statistic is also higher than table value at 99% level of significance indicating that there is a presence of relationship, as adjusted : 0.37912. The observed adjusted shows that the issues regarding administrative efficiency of VAT and other independent variable is affected administrative efficiency for VAT collection to the extent of 39.1% point. It shows that the variation in dependent variable is explained to 37% by the variables of independent variables included in the model